"Avatar to Person" (ATP) Virtual Human Social Ability Enhanced System for Disabled People. (3rd December 2021) - Guo, Zichun; Wang, Zihao; Jin, Xueguang
Abstract : How to make communication more effective has been underlined unprecedentedly in the artificial intelligence (AI) era. Nowadays, with the improvement of affective computing and big data, people have generally adapted to construct social networks relying on social robots and smartphones. Although the technologies above have been widely discussed and used, researches on disabled people in the social field are still very limited. In particular, facial disabled people, deaf-mutes, and autistic patients are still meeting great difficulty when interacting with strangers using online video technology. This project creates a virtual human social system called "Avatar to Person" (ATP) based on artificial intelligence and three-dimensional (3D) simulation technology, with which disabled people can complete tasks such as "virtual face repair" and "simulated voice generation, " in order to conduct face-to-face video communication freely and confidently. The system has been proven effective in the enhancement of the sense of online social participation for people with disabilities through user tests. ATP is certain to be a unique area of inquiry and design for disabled people that is categorically different from other types of human-robot interaction.